Massive ductal aneurysm in an asymptomatic child with Loeys-Dietz syndrome - Siddiqui, Saira (Ann Pediatr Cardiol, 2021)
An asymptomatic 3-year-old with Loeys-Dietz Syndrome (LDS) followed for a small patent ductus arteriosus and dilated aorta was found to have a massive ductal aneurysm on routine surveillance cardiac magnetic resonance. The aneurysm was successfully resected. Serial advanced imaging tools are useful in surveillance, diagnosis, and management in patients with LDS.